Kebutuhan untuk Pemulihan Dalam Perspektif Perilaku Organisasional: Sebuah Studi Literatur - Wahyu Rusdiyanto; Mugi Harsono (Jurnal Manajemen DIVERSIFIKASI, 2024)
This article discusses the concept of the need for recovery in the context of work well-beingand productivity. Understanding the need for recovery is expected to help design effectivestrategies for managing work stress, improving employee performance, and buildingorganizational resilience to unexpected events. This research uses a qualitative approachwith a literature study design. This article discusses the significant implications the need forrecovery has on individuals and organizations, and provides practical suggestions fordesigning work environments that support employee recovery. In conclusion, awareness andsupport of recovery needs not only creates a productive work environment but alsocontributes to employees' work and personal life balance. The recovery program initiative isexpected to be a competitive force for organizations in achieving long-term growth andsustainability.